About The Renowned Recitation Imam Asim Ibn An-Najud - Ruziev Jahongir Okhtamovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article discusses the life and scholarly activities of the famous Qur'anic reciter, Asim ibn Abu al-Najud al-Kufi. He is recognized as one of the leading scholars in the fields of recitation and grammar, and was a prominent reciter among the Tabi'in of his time. Valuable information about Asim's life, his intellectual legacy, related narratives, and his contemporaries is presented. Additionally, the article discusses his notable students and their contributions to recitation. The significance of the science of recitation and its role within the Muslim community, as well as the differences between shazz and mutawatir recitations, are also elaborated upon.